Haemozoin Deposits Influence Fetal Weight of Pregnant Mice Infected by Plasmodium berghei - Andari, Desy; Fitri, Loeki E; Mintaroem, Karyono (Jurnal Kedokteran Brawijaya, 2015)
Low birth weight is commonly attributed to malaria in pregnancy, but the cellular and molecular mechanisms that underlie this are incompletely understood. Many of hormones and cytokines are dysregulated in this case and it alters histological structure of placenta which known as placenta malaria. In the placenta malaria, there is an accumulation of infected erythrocytes, macrophages and malarial pigment (haemozoin). This study was conducted to compare the levels of plasma and placenta interferon-gamma (IFN-Î³) and haemozoin deposit in pregnant mice that infected by Plasmodium berghei (treatment group) to the normal pregnant mice (control group) and its association with fetal weight. This in vivo experimental laboratory study used pregnant Balb/c mice which divided to control and treatment group. Placentas were staining with Haematoxylin-Eosin (HE) for haemozoin deposits examination. Plasma and placenta levels of IFN-Î³ examined with ELISA assay. Levels of IFN-Î³ were higher in plasma than placenta and slightly higher in treatment group than control group, but the differences were not significant (p>0,05). Fetal weight of treatment group was lower than those of control group (p=0,002) however there was no correlation between fetal weight and plasma as well as placenta levels of IFN-Î³ (p>0,05). Haemozoin deposit was found only in treatment group and influenced weight of fetuses (Spearman=-0,633, p=0,006). Weights of fetuses are more interfered by haemozoin deposit and seemly not by plasma and placenta levels of IFN-Î³ during malaria infection.Keywords: Fetal weight, gamma interferon, haemozoin, malaria, placenta